(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The issue addressed in this study revolves around the low level of student interest, particularly in Islamic Religious Education, which is primarily due to the lack of innovative teaching media. As a result, the material delivered by the teacher often fails to capture students’ attention effectively. Therefore, the aim of this study is to explore the impact of using Kahoot as a learning tool to enhance student interest in Islamic Religious Education at SMP Negeri 1 Payakumbuh, as well as to identify the factors that support and hinder the use of Kahoot in this context. This research employs a qualitative approach with a case study design, utilizing data collection methods such as observation, documentation, and interviews. The findings of the study suggest that Kahoot has a significantly positive effect on boosting student engagement in Islamic Religious Education. Supporting factors include students’ familiarity with technology, sufficient facilities, and qualified teachers, while the challenges include occasional network instability and time limitations.